PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN MOTOR HONDA PADA PT. DAYA ANUGRAH MANDIRI PAREPARE - Dinsar, Arfandy (Universitas Muhammadiyah Parepare, 2020)
The purpose of this study is to determine the service quality which have a partial and simultaneous effect on Honda Motorcycles customer satisfaction at PT. Daya Anugrah Mandiri Parepare. The method of analysis used is to use validity test, reliability test, multiple linear regression, partial test, simultaneous test, determination test (Rsquare). Data collection techniques in this study are the method of observation, questionnaires, interviews and documentation. In this study, the population is consumers of Honda motorcycles at PT. Daya Anugrah Mandiri Parepare, amounting to 60 people. The results showed that (1) Physical Evidence (X1), the test results shows that the value of t = (-0.221) with a significance value of 0.826 > 0.05; (2). Reliability (X2), the test results shows that the value of t = (-0.530), with a significance value of 0.598 > 0.05; (3). Responsiveness (X3), the test results shows that the value of t = 5.974, with a significance value of 0.000 > 0.05; (4). Guarantee (X4), the test results shows that the value of t = 0.223. with a significance value of 0.824 > 0.05; (5). Empathy (X5), the test results shows that the value of t = 0.675, with a significance value of 0.502 > 0.05; (6) Physical evidence, reliability, responsiveness, guarantee and empathy have a positive effect and significant (0.000 < 0.05) simultaneously on customer satisfaction.